The Effect of Accounting Information System Quality, Service Quality and System Security on User Satisfaction of M- Banking Based Applications at Bank Sumsel Babel - Wijayanti, Feliantika; Terzaghi, Muhammad Titan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to analyze the effect of accounting information system quality, service quality and system security on user satisfaction of m-banking-based applications at Bank Sumsel Babel. This research uses descriptive methods with a quantitative approach. The population in this study were customers who used mobile banking at Bank Sumsel Babel, with as many as 198,017 customers. The number of samples taken in this study was 400 respondents. The sampling technique was carried out using the Slovin technique, namely the random sampling method (random sampling technique). The type of data used in this study is primary data collected directly through the data collection process using the distribution of questionnaires using Google Forms. The results showed that the quality of accounting information systems, service quality, and system security had a positive and significant effect on user satisfaction of m-banking-based applications at Bank Sumsel Babel and simultaneously that the quality of accounting information systems, service quality and system security had a positive and significant effect on user satisfaction of m-banking-based applications at Bank Sumsel Babel